Analysis of user interaction with virtual objects in augmented reality applications - M. V. Alpatova (E-Management)
The paper proposes approaches for analyzing user interaction with augmented reality objects and describes the results obtained from implementing the developed methods for optimal placement of virtual objects in augmented reality applications in practice. A large amount of collected experimental data is statistically analyzed to make sure that the previously proposed method of optimal augmented reality object placement really simplifies the user experience and reduces the time needed for object placement. The results of this analysis allow us to conclude the effectiveness of the proposed method. The current challenges of applications which implement augmented reality technology in the field of user experience and their solutions are also discussed. This research is conducted to find new methods for developing applications and services that present features to the user by applying augmented reality technology. Currently, there are many different algorithms that allow the recognition of anchor points in flat images and in space. However, at a higher level, there are many research tasks for developers on the most effective application of these algorithms and subsequent analysis of the data obtained. The active expansion of augmented reality and its gradual introduction into many areas of human activity is generating new topical challenges, which is the reason for the investigation of the described field in the present article.